Readiness Of The Application Of E-Management In The Public Service Sector: An Analytical Study Of A Sample Of Employees In The Organizations Of Water And Electricity In The Province Of Diwaniyah - Abdul-Resoul, Hussein A.; Kazim, Ilham N. (Humanities Journal of University of Zakho, 2018)
The present study aims to investigate the possibility of application of e- management mechanisms from the perspective of employees in the organizations of water and electricity in the province of Diwaniyah, through reliance on technology acceptance model (TAM), which determines the readiness of the application of information technology in organizations through knowledge to guide to both ( interest perceived, perceived ease, the positions of use, intention to use) and selected a random sample of employees amounted to (109) an individual to verify hypotheses. The questionnaire was used as a tool head of the study according to the measure (Adesina, 2010). The data was analyzed according to the statistical methods (such as factor analysis, and composite reliability coefficient) according to the style of structural equation modeling. The study concluded agreement and intention of the sample towards the application of e-management. It is based on It recommended the necessity of adopting senior management in government departments in general and service organizations, in particular, the requirements of the application of e-management.